Notalina roraima Holzenthal 1986 (Trichoptera: Leptoceridae), male genitalia variability and larval description - Zamora-Muñoz, Carmen; Derka, Tomáš; Cressa, Claudia (Zootaxa, 2013)
Notalina roraima Holzenthal 1986 was described on the basis of a single holotype specimen from the Pantepui Region. The species is a member of the endemic Neotropical long-horned caddisfly (Trichoptera: Leptoceridae) subgenus Notalina (Neonotalina) Holzenthal 1986. We present new records of this species and describe some morphological variation in the male genitalia. Moreover, we describe and illustrate the larva of this species and include information of its habitat. We also differentiate it from N. morsei, the only larva of the subgenus Neonotalina described until now.